Thiazole yellow G dyed PVA films for optoelectronics: microstructrural, thermal and photophysical studies. (21st July 2016) - Hebbar, Vidyashree; Bhajantri, R F; Naik, Jagadish; Rathod, Sunil G
Abstract: In this paper, we report the microstructural, optical and fluorescence properties of poly(vinyl alcohol) (PVA)/Thiazole Yellow G (TY) dye composite prepared by solvent casting. The formation of change-transfer complex as a result of the interaction between the dye molecules and polymer chain is confirmed in FTIR, FT-Raman, XRD and DSC studies. SEM studies present the morphology of the samples. The UV-visible absorption spectra possess characteristic peaks of the TY dye corresponding to n - π * transition along with a characteristic peak of PVA. The composites exhibit the decreasing energy gap and increasing refractive index with an increase in wt.% of the TY dye. The fluorescence-quenching phenomena are observed in emission wavelength range of 391–406 nm upon excitation in the vicinity of absorption maxima (335 nm) with the quantum yield of 0.72 for lowest concentration of dye. The prepared composites bear high brightness, and improved thermal stability, which make them a promising material for sensors and optoelectronic applications.